Działania Unii Europejskiej na rynku pracy w świetle pogłębiania integracji europejskiej - Cybulski, Leszek (The EU Actions in the Labour Market and the Deepening of European Integration, 2009)
Among economic, legal and geographical aspects of European integration, the European Union institutions also increased their role in the labour market. This paper presents types of these activities and shows the evolution of European employment policy. It also signals threats coming from the increased expectations for the EU and lower acceptance for the deepening process of integration. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 560-568